Similarity evidence between the country risk and the idiosyncratic risk: An empirical study of the Brazilian case - André Assis de Salles (Economic Journal of Emerging Markets, 2021)
Purpose - This paper estimates the idiosyncratic risk (IDR) time series in the Brazilian economy and verifies its interaction with the Brazilian country risk indicators, measured by the EMBI+ (the Emerging Markets Bond Index).Methods - This paper estimates various regression models to capture the dynamic nature of the variables. The models include the heteroscedastic conditional autoregressive models and vector error correction models (VECM). Findings - The results show similarities or associations between the two indicators with interactions in the short and long run. The idiosyncratic risk proves to be a relevant indicator of the risk of economic activities implemented within the scope of the Brazilian economy and can help evaluate investments in related projects. This results also provide evidence of cointegration between the EMBI+ and IDR variations.Implication - This result suggests an alternative way for obtaining estimates of the expected return required by economic agents in financing and investing in productive and infrastructure projects necessary for developing the Brazilian economy that provides greater employability and good social welfare.Originality - This paper provides an alternative estimate of the time series proxy of idiosyncratic risk in the Brazilian economy. It also compares the results with the time series results obtained from the country risk measure EMBI+, widely used among resource managers in the international markets.